THE EFFECT OF POSITIVE PSYCHOLOGICAL INTERVENTION IN IMPROVING PSYCHOLOGICAL WELL-BEING OF THE ELDERLY IN THE PADU WAU MAUMERE ELDERLY SOCIAL WELFARE CENTER - Yunita, Marta; Nancy, Maria Nona; Akintomide, Gabriel Akinjide (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
Abstract The implementation of student internship activities takes place at the Padu Wau Maumere Elderly Social Welfare Home which is located in Watumilok Village, Kangae District, Sikka Regency, East Nusa Tenggara. The internship was carried out for 3 months, starting from September 02 to December 20, 2024. The research was conducted during data collection and intervention. This study proves that positive psychology intervention using forgiveness therapy, gratitude and relaxation techniques are factors that contribute to psychological well-being. This is supported by the results of the Wilcoxon test which showed a figure of 0.027<0.05, this proves that this intervention has an effect on the elderly who experience Psychological Well Being at the Padu Wau Maumere Elderly Social Welfare Home.   Keywords:Elderly, Positive Psychology Interventions, Psychological Well-being